Modern challenges in ensuring the security of the Kyrgyz Republic in the context of modernization “Processes” (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
The article discusses the dynamics of the political process, the stages of modernization, and the main periods and factors of influence on the transformation in modern Kyrgyzstan. After the disintegration of the Soviet Union in 1991 a rapid transformation processes of political and economic systems started in Kyrgyzstan under the influence of external power centers and internal nationconstruction. The transit time in the Kyrgyz Republic took its origin with the restarting of the national state and the process has been going on up to the present time.
Keywords: transformation, modernization, development dynamics, modern Kyrgyzstan, political process, crisis, constitution